Worldwide prevalence estimates of burning mouth syndrome: A systematic review and meta‐analysis - Wu, Shuangshuang; Zhang, Wenqing; Yan, Jingxian; Noma, Noboru; Young, Andrew; Yan, Zhimin (Oral diseases, 2022)
Objectives To evaluate the worldwide prevalence and epidemiology profile of burning mouth syndrome. Material and Methods A systematic review and meta‐analysis was conducted. Search strategies were performed in PubMed, EMBASE, Web of Science, the Cochrane Library, China National Knowledge Infrastructure, and Wanfang database for studies published before January 31, 2021, for the prevalence of burning mouth syndrome. Results Eighteen articles were included. The overall pooled prevalence of burning mouth syndrome was 1.73% (95% CI = 0.176–0.351, n = 26,632) in general population, and 7.72% (95% CI = 0.434–0.691, n = 86,591) in clinical patients. The subgroup analysis by continent showed that among the population‐based studies the prevalence in Asia (1.05%) lower than in Europe (5.58%) and North America (1.10%). The subgroup analysis by gender showed the prevalence of female (1.15%) was higher than male (0.38%) in general population. The subgroup analysis by age showed the prevalence was higher for people over 50 (3.31%) than under 50 (1.92%). Conclusions The pooled prevalence of burning mouth syndrome was relatively high in both general population and clinical patients, varies in different regions with the highest prevalence in Europe, and females over 50 years were the most susceptible group. More epidemiological surveys on the prevalence of burning mouth syndrome are needed.